2019
DOI: 10.3390/jcm8060798
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Investigation of β-Thalassemia in Chorionic Villi Samples

Abstract: Background: Beta-thalassemias are blood disorders characterized by poorly understood clinical phenotypes ranging from asymptomatic to severe anemia. Metabolic composition of the human placenta could be affected by the presence of pathological states such as β-thalassemia. The aim of our study was to describe metabolic changes in chorionic villi samples of fetuses affected by β-thalassemia compared to a control group by applying a metabolomics approach. Methods: Chorionic villi samples were differentiated accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…One approach to identifying novel biomarkers of disease uses metabolomics in a combination of analytical and biochemical techniques [12]. Nuclear magnetic resonance spectroscopy (NMR) and mass spectrometry (MS) are the most frequently employed techniques in metabolomics and are powerful methods for differentiating the diversities between cases and controls [13,14]. Bioinformatics increases the value of metabolomic analysis by assessing general biochemical and signaling pathways that may be altered in disease states [15].…”
Section: Introductionmentioning
confidence: 99%
“…One approach to identifying novel biomarkers of disease uses metabolomics in a combination of analytical and biochemical techniques [12]. Nuclear magnetic resonance spectroscopy (NMR) and mass spectrometry (MS) are the most frequently employed techniques in metabolomics and are powerful methods for differentiating the diversities between cases and controls [13,14]. Bioinformatics increases the value of metabolomic analysis by assessing general biochemical and signaling pathways that may be altered in disease states [15].…”
Section: Introductionmentioning
confidence: 99%
“…Untargeted lipidomics approaches have emerged as a useful tool for the discovery of underlying disease mechanisms and novel biomarkers [32,33]. Only a few metabolomics studies have been conducted in thalassemia patients, yet none used a comprehensive untargeted lipidomic approach, and only one study was conducted using adult thalassemia patients [17,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, phenotypic or genetic heterogeneity can make prenatal diagnosis difficult (e.g., β-thalassemia, Noonan's syndrome). Nonetheless, Monni et al found that pregnancies affected by β-thalassemia exhibit significant metabolic changes (123).…”
Section: Single-gene Disordersmentioning
confidence: 99%